Penguatan Karakter Islami Siswa melalui Pembiasaan Shalat Dhuha di Madrasah Ibtidaiyah Tarbiyatul Athfal Pangkalan - Asep Supriatna; Saepudin; Riki Faisal; Hani Nurhayanti; Dede Sarim (Bulletin of Community Engagement, 2024)
The low level of discipline and awareness of prayer among students shows the importance of efforts to strengthen Islamic character from an early age. This Community Service Activity (PKM) aims to strengthen the Islamic character of students at Madrasah Ibtidaiyah Tarbiyatul Athfal Pangkalan through the habit of Dhuha prayers. The main problem faced is the lack of consistent application of religious values, especially in building sustainable habits of worship. This program is expected to increase students' religious awareness and form an attitude of discipline and responsibility through worship routines. The underlying concept is a spirituality-based character education theory, which emphasizes habituation as an effective method for internalizing values. The methods used include carrying out Dhuha prayers in congregation, teacher assistance, and evaluating student development. The results show a significant increase in students' discipline, sincerity and independence in carrying out their worship. Apart from that, this activity contributes to creating a school environment that is conducive to learning Islamic values. The habit of Dhuha prayer has proven to be effective as a means of forming religious character that can continue in the home environment.